Providing an in vitro depiction of microglial cells challenged with immunostimulatory extracellular vesicles of Naegleria fowleri - Retana Moreira, Lissette; Cornet-Gomez, Alberto; Sepulveda, M. Rosario; Molina-Castro, Silvia; Alvarado-Ocampo, Johan; Chaves Monge, Frida; Jara Rojas, Mariana; Osuna, Antonio; Abrahams Sandí, Elizabeth (Frontiers in Microbiology, 2024)
Naegleria fowleri is the causative agent of primary amoebic meningoencephalitis, a rapid and acute infection of the central nervous system with a fatal outcome in >97% of cases. Due to the infrequent report of cases and diagnostic gaps that hinder the possibility of recovering clinic isolates, studies related to pathogenesis of the disease are scarce. However, the secretion of cytolytic molecules has been proposed as a factor involved in the progression of the infection. Several of these molecules could be included in extracellular vesicles (EVs), making them potential virulence factors and even modulators of the immune response in this infection. In this work, we evaluated the immunomodulatory effect of EVs secreted by two clinic isolates of Naegleria fowleri using in vitro models. For this purpose, characterization analyses between EVs produced by both isolates were first performed, for subsequent gene transcription analyses post incubation of these vesicles with primary cultures from mouse cell microglia and BV-2 cells. Analyses of morphological changes induced in primary culture microglia cells by the vesicles were also included, as well as the determination of the presence of nucleic acids of N. fowleri in the EV fractions. Results revealed increased expression of iNOS, proinflammatory cytokines IL-6, TNF-α and IL-23, and the regulatory cytokine IL-10 in primary cultures of microglia, as well as increased expression of iNOS and IL-13 in BV-2 cells. Morphologic changes from homeostatic microglia, with small cellular body and long processes to a more amoeboid morphology were also observed after the incubation of these cells with EVs. Regarding the presence of nucleic acids, specific Naegleria fowleri DNA that could be amplified using both conventional and qPCR was confirmed in the EV fractions. Altogether, these results confirm the immunomodulatory effects of EVs of Naegleria fowleri over microglial cells and suggest a potential role of these vesicles as biomarkers of primary acute meningoencephalitis.